2000
DOI: 10.1515/cclm.2000.033
|View full text |Cite
|
Sign up to set email alerts
|

On Accuracy and Precision of a HPLC Method for Measurement of Urine Porphyrin Concentrations

Abstract: We studied the accuracy and precision of a HPLC method for determination of porphyrins in urine. A commercial standard solution appeared to contain less porphyrins than indicated by the manufacturer, since calibration resulted in lower concentrations of uroporphyrin and coproporphyrin: 16% and 8%, respectively. Coefficients of variation for the measurement of uro-, hepta-, copro I and copro III porphyrins in samples of patients with and without porphyria were often much less than 15%. Comparison of measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Levels of CP in the patient urines were observed about two times higher than those of healthy persons. The significant increase of CP in patient urine was consistent with that previously reported for patients with liver disease, [46] indicating that the determination of CP in human urine might be served as a diagnostic symptom of liver disease. It was also observed that the levels of HEXAP and PENTAP in the patient urine samples were significantly higher than those in healthy human urine.…”
Section: Determination Of Porphyrins In Human Urinesupporting
confidence: 89%
“…Levels of CP in the patient urines were observed about two times higher than those of healthy persons. The significant increase of CP in patient urine was consistent with that previously reported for patients with liver disease, [46] indicating that the determination of CP in human urine might be served as a diagnostic symptom of liver disease. It was also observed that the levels of HEXAP and PENTAP in the patient urine samples were significantly higher than those in healthy human urine.…”
Section: Determination Of Porphyrins In Human Urinesupporting
confidence: 89%
“…For URO this has been shown before. 4 Using these results, we conclude that commutable calibrators are needed to improve the laboratory diagnosis of porphyria. Using such calibrators the inter-laboratory CVs should decrease.…”
Section: Resultsmentioning
confidence: 85%